COMPARISON OF STUDENT LEARNING OUTCOMES IN THE APPLICATION OF METHODINDEX CARD MATCH BY METHOD STUDENT TEAMS ACHIEVEMENT DIVISION ON THE SUBJECT OF FIQH IN MTS AS'ADIYAH BRANCH NO.60 LATTIMU WAJO REGENCY - Fitri Ramadan; Wardana Wardana; Zakaria Zakaria (Education Studies and Teaching Journal (EDUTECH), 2025)
Improving the quality of Islamic Jurisprudence (Fiqh) learning in Islamic schools requires the implementation of learning methods that can encourage active student involvement. This study aims to compare student learning outcomes between the Index Card Match (ICM) and Student Teams Achievement Division (STAD) methods in Fiqh learning at MTs As'adiyah Cabang No. 60 Lattimu, Wajo Regency, Indonesia. Using a quantitative approach with a quasi-experimental design, this study involved two classes, each of which was given a different learning method. The results showed significant differences in student learning outcomes between the two methods. The ICM method increased individual active participation through question-and-answer card matching activities, while the STAD method encouraged collaborative learning through heterogeneous group discussions and individual quizzes. Both methods were effective in improving Fiqh learning outcomes, but the ICM method showed a higher increase in learning outcomes. These findings indicate that an interactive and student-centered learning approach is more effective in strengthening understanding of Fiqh material. This study emphasizes the importance for educators to adopt innovative and varied learning strategies to optimize student learning outcomes.